Linear porokeratosis in a 2-year old Hispanic female. - Saley, T.P.; Shendrik, I.; Blalock, T.W. (European Journal of Pediatric Dermatology, 2015)
Linear porokeratosis is an uncommon form of porokeratosis clinically characterized by linearly arranged lesions with an atrophic center surrounded by a peripheral hyperkeratotic rim and histologically by a cornoid lamella. The clinical course is variable, the sensitivity to the therapy is different in the various patients and a malignant degeneration is possible. Here is reported a case in a 2-year old little girl.